A produção do espaço habitado pela comunidade ribeirinha de Boa Esperança no rio Xingu-Altamira-Pará - SOUSA FILHO, Hudson Nascimento de (Universidade Federal do Pará, 2023)
This research addresses issues that arise from the production of the space inhabited by the riverside community of Boa Esperança, located in an archipelago of river islands upstream from the city of Altamira-Pará on the Xingu River. Being located in low latitudes, this community has a short dry season tropical climate regime (am type climate), with stilt houses that occupy the plains that are influenced by the flood regime of the river, the "beiradão", which also offer fertile fields for polyculture agricultural activities. Thus, in general, this research work seeks to understand the production process of the space inhabited by the riverside community of Boa Esperança, at first, enumerating the aspects of the landscape in the daily life of the community, as well as, in addition to these objectives adds the construction of a certain reflexive analysis on the work relations that attribute functionality to the territorial configuration of the community. It was sought to build a certain analysis focused on spatial dynamics with the empirical observation of the socio-environmental conditions existing in the daily life studied and, for this, the research team relied on the application of form interviews and the lifting of aerial images obtained with a drone that helped in the observation of the landscape. Thus, the fact that field research activities have been built with the intention of structuring data and collecting information of spatial historical, socioeconomic and environmental relevance on the context in which the living conditions of the riverside community are developed is mentioned. of Good Hope. This, in turn, shows traces of their ancestry linked to the rubber tappers who migrated from the Northeast to work in the rubber plantations of the middle Xingu, extracting latex mainly from the native rubber trees of the region in the mid-nineteenth century, the decade 1870. Since then, labor activities such as extractivism, burning and artisanal fishing have been the basis of livelihood and trade for riverside families that were constituted with the territorialization of the aviamento system in the region, at the time of the first cycle of the rubber economy.